(3eONd fXe GdeYdheGJs - (3eMeO YHGS(B, (3HOhjs; (3YHO GdhgGH fUQ Ydj(B, s ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2008)
(3CSGSjGJ GdeMGSHI GdeGdjI cfXGe ddeYdheGJ, WHjYI GdeMGSHI cfXGe ddeYdheGJ h CSS JTZjd GdbWGY GdeMGSHj, GdeMGSHI aj GdeTQhY GdJLGQj h aj GdeTQhY GdUfGYj, GdJMUjd h GdSOGO HGSJNOGe GdChQGb GdeGdjI, GdjhejGJ GdNGUI h GdMSGHGJ GdeSGYOI h GdGLeGdjI, GdJShjGJ GdLQOjI h JMdjd GdbhGFe GdeGdjI, LQO h JShjI GdNUhe, GdeNRhf , GdCUhd GdKGHJI h GdNUhe, GdCNWGA GdeMGSHjI h cjajI eYGdLJgG, bQGAI h JMdjd GdJbGQjQ GdeGdjIs
((3GbJfGAGJ (B2014 1(3f(B)s
Keywords: (3GdeGdjI GdYGeI(B-(3eMGSHIs; (3GdeMGSHI GdJMdjdjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s